Up in flames: a flammability assessment of alcohol-based hand sanitizers on common perioperative materials - Almengor, Samuel; Monaghan, W. Patrick; FL, Jacksonville (International Journal of Advanced Nursing Studies, 2015)
Introduction: The objective of this study was to perform a flammability assessment of alcohol-based hand sanitizers on common perioperative materials. There is an estimated 550â€“650 surgical fires that occur nationally each year, an instance comparable to that of wrong-site surgery, yet only about 100 operating room fires are reported each year.Â The median cost of an OR fire settlement claim is 120,166.Â Generation of fire requires the presence of three components, known as the â€œfire triadâ€: (1) an oxidizer, (2) an ignition source, and (3) fuel.Methods: The flammability of five common perioperative materials was assessed (conform stretch gauze, surgical drape, foam headrest, OR towels, and lap sponges).Â The flammability of these materials was assessed alone and with six test liquids (Purell Advanced, Germ-X, generic hand sanitizer, spray hand sanitizer, ChloraPrep, and sterile water).Â The assessments with the test liquids were conducted immediately after application and after five minutes.Â The ignition sources used were a lighter and two spark generators (piezo-electric and battery-powered spark generator).Results: Two of the five perioperative materials were easily ignitable (OR towels and lap sponges), while the others exhibited flame retardant properties, which manifested itself as â€œmeltingâ€ when an ignition source was applied (conform stretch gauze, surgical drape, and foam headrest).Â ChloraPrep served as the positive control and sterile water served as the negative control.Â When alcohol-based hand sanitizers and ChloraPrep were added to these materials, the flammability increased.Â The addition of sterile water to the perioperative materials rendered the material nonflammable. The piezo-electric spark generator did not elicit any combustion of perioperative materials with or without test liquids, but the battery-powered spark generator did.Conclusion: Commonly used alcohol-based hand sanitizers are flammable.Â When alcohol-based hand sanitizers are applied to perioperative materials, their flammability increases, even materials which were previously nonflammable.Â Electrostatic discharge did illicit combustion of alcohol-based hand sanitizer on any perioperative materials tested, and should be recognized as a genuine safety hazard.Â Although these personal hand sanitizer products are commonly used for their antiseptic properties, one should exercise prudence with their use to avoid causing harm to the patient.